An exploratory study of consumer attitudes towards mobile ticketing in Sweden - Tatjana Apanasevic; Jan Markendahl; Niklas Arvidsson (International Telecommunications Society (ITS), 2013)
Swedish public transport organizations have set an objective to double usage of the public transport during the next coming five years. This study attempts to investigate if the current ticket solutions support the goal of the public transport companies, and if the available mobile phone solutions can lower barriers for consumers. In order to do that, critical travelling moments for users of different market segments were estimated during a pre-study stage. The following focus group discussions helped to validate problems identified during the pre-study. At the same time, focus groups provided deeper consumer insights on general consumer perception of the transport service, ticketing, mobile payment, quality of service, consumer expectations related to the public transport services, and consumer satisfaction and loyalty. The conducted research helped to identify problems existing in public transport ticketing and mobile payment areas, which have the negative impact on the usage of the public transport service and contribute with additional barriers for users. Moreover, this conclusion is supported by multiple examples that clearly illustrate what does not work, and why it does not work. Hence, mentioned solutions do not support the overall objective of the public transport operators. The comprehension of these problems and barriers can contribute to a better understanding of consumer needs and expectations, and help the public transport service providers to improve the service.
Keywords: 330; Mobile Payment Services; Public Transport; Public Transport Ticketing; m-Ticketing; Focus Group; Consumer Expectations of a Service; Perception of a Service; Quality of Service; Customer Satisfaction; Loyalty